Language Inequality: Machine Translation as the Bridging Bridge for African Languages (2013)
African languages are losing their status, functions and role in African society because of the appreciable status and power of foreign and colonial languages. There is a wide gap between African languages and the foreign colonial languages in almost all areas of use in the Africa; This paper explores the possibility of Information and Communication Technology (ICT) and specifically Machine Translation (MT) to bridge the imaging gaps between these two categories of languages. As much as MT would do that, there are lots of impeding challenges about its use in Africa and this paper gives some insight in this regard.